Prenatal glomerular changes during development of human foetal kidney - Roli Joshi; Deepa Deopa; D N Sinha; A K Singh (Wolters Kluwer Medknow Publications, 2016)
Background and aims: The cortical glomerulus shows many developmental changes during fetogenesis. Normal histology of the fetal glomerulus at various stages of development was studied to get insight into the morphology of fetal glomerulus. Fetal glomerular study is a necessity for correlation with increase in gestational age and pathological changes which may affect the normal functioning of kidneys in fetal life. Method: Dissection of 70 normal human fetuses was carried out and histological findings of glomerulus were noted with respect to the age of fetus. The histology of fetal kidney was studied using H & E stain. Important developmental stages of glomerulus were observed. Results: Fetal kidney glomerulus histology is different from adult. Unlike in adult kidney, foetal kidney glomerulus shows many developmental stages as v, c, s, cresentric in starting phase. Multiple rows arrangement in between medullary rays with well developed mature glomeruli at juxtamedullary junction. Capillary invagination with developed Juxta glomerular apparatus was appreciated. Nephrogenic zone which was found as broad band in early gestational weeks disappeared near term. Conclusion: The present study will be helpful in understanding the normal histological architecture of foetal kidney glomerulus and add to the existing knowledge regarding development of foetal kidney, its relation with gestational age and pathogenesis.